Impact of heated tobacco products, e-cigarettes, and combustible cigarettes on small airways and arterial stiffness - Goebel, Isabel; Mohr, Theresa; Axt, Paul N.; Watz, Henrik; Trinkmann, Frederik; Weckmann, Markus; Drömann, Daniel; Franzen, Klaas F. (Toxics, 2023)
Smoking cessation is difficult but maintaining smoke-free without nicotine replacement therapy is even harder. During the last few years, several different alternative products, including heated tobacco products (HTP), have been introduced to the market. In this study, we investigated the acute effects of IQOSTM and gloTM (two HTP) consumption on small airway function and arterial stiffness in a head-to-head design, comparing them to combustible cigarettes, nicotine-free e-cigarettes and a sham smoking group. Seventeen healthy occasional smokers were included in a single-center, five-arm, crossover study. The parameters of small airway function and hemodynamics were collected at several time points before and after consumption using Mobil-O-Graph™ (I.E.M., Stolberg, Germany) and TremoFlo® c-100 (THORASYS Thoracic Medical Systems Inc., Montreal, QC, Canada). Small airway obstruction and resistance were both significantly increased after the consumption of cigarettes and substitute products. All products containing nicotine led to similar significant increases in blood pressure and arterial stiffness. Hemodynamic parameters were also increased after the consumption of e-cigarettes without nicotine, but compared to nicotine-containing products, the increase was shorter and weaker. We conclude that, although it has yet to be determined why, HTP have acute harmful effects on small airway function, possibly even exceeding the effects of combustible cigarettes. Like other nicotine-containing products, HTP leads to a nicotine-related acute increase in arterial stiffness and cardiovascular stress, similar to combustible cigarettes, which associates these products with an increased cardiovascular risk.